Benchmarking on supply chain partnering effectiveness in two semiconductor companies: a case study approach - Rajagopal, Premkumar; Zailani, Suhaiza; Sulaiman, Mohamed (Emerald Group Publishing, 2009)
Purpose – Supply chain partnering (SCP) in internationally operating companies is still not adequately addressed in the literature. The purpose of this paper is to examine the factors towards effective SCP across two organizations of different origins (Company A and Company B). Design/methodology/approach – The central issue is to investigate how information flow, organizational linkage, supply chain infrastructure, and resource sharing exhibit themselves in the SCP through a case study method. Findings – The interviews reveal that Company B tends to be a reluctant player and is far more skeptical about the benefits afforded through such a relationship. It can also be concluded that Company B is less interested in the benefits gained and is more likely to highlight the risks associated with heightened dependence on a smaller number of suppliers. On the one hand, it can be stated that Company B thinks about the gains afforded by partnering supply chains but is more easily swayed by traditional purchasing metrics related to cost or initial purchase prices. On another level, Company A seems to fully participate in SCP efforts and sees the benefit from such a relationship. Research limitations/implications – The interviews are necessary for developing basis understanding on how companies implement SCP, especially to examine the factors that contribute to its successful. The study suggests that larger number of sample need be used. Practical implications – From the case study, it is believed that firms appear to confirm a positive and significant relationship between the degree of resource sharing and organizational linkage, if they see that scalable partnering efforts as hypothesized are workable. Originality/value – The case study highlights is the important role of the partnering to support supply chain process and to deliver high-quality service. This is important because the profitability and survival of the chains depend on how well partnering concept been implemented.